Evaluating the Impact of Economic Programs on the Transformation of Mustahik into Muzaki: A Case Study of the National Zakat Agency (BAZNAS) - Mumuh Muhammad; Rida Rosida; Firmansyah; Rifka Aulia (Tazkia Islamic Finance and Business Review, 2025)
Poverty constitutes a multidimensional challenge faced by numerous countries, including Indonesia. It not only affects the economic conditions of society but also exerts a profound impact on overall quality of life and national development, encompassing socio-political dynamics, education, and healthcare services. The poverty cycle can only be disrupted through a holistic intervention strategy, which extends beyond financial approaches and incorporates integrated support mechanisms, including active participation from various stakeholders. This study aims to evaluate the role of the National Zakat Agency (Badan Amil Zakat Nasional/BAZNAS) in transforming the status of mustahik (zakat recipients) into muzaki (zakat payers) through its implemented economic empowerment programs. A descriptive method with a quantitative approach was employed to assess the impact of these programs on the transformation process from mustahik to muzaki. The findings indicate a significant correlation between BAZNAS’ economic programs and the transformation of mustahik into muzaki. Therefore, it is imperative for BAZNAS to strengthen the governance of its economic programs and ensure continuous mentoring for mustahik, so that this positive relationship can be sustained and deliver more optimal, long-term benefits